Application of Luminex Gastrointestinal Pathogen Panel to human stool samples from Côte d’Ivoire - Veronica Di Cristanziano; Monika Timmen-Wego; Nadine Lübke; Rolf Kaiser; Herbert Pfister; David Di Cave; Federica Berrilli; Yolande Kaboré; Rossella D´Alfonso (Journal of Infection in Developing Countries)
Introduction: Gastrointestinal infections caused by viruses, bacteria, and parasites are endemic in most developing countries due to inadequate provision of safe water supplies, sanitation, and hygiene. To investigate the enteric pathogens infecting people living in Côte d’Ivoire, the Luminex Gastrointestinal Pathogen Panel (xTAG GPP) assay was used to analyze 34 human fecal samples. This study represents the first application of this technology to samples from a sub-Saharan African country. Methodology: Thirty-four stool samples from asymptomatic and symptomatic patients, 1–15 years of age, were analyzed by xTAG GPP. The Luminex assay represents a qualitative bead-based multiplexed molecular diagnostic test able to identify concurrently 15 enteric pathogens, including bacteria, viruses, and parasites. Results: Overall, 22 out of 34 (64.7%) fecal specimens were detected to be positive by xTAG GPP. Sixteen were from asymptomatic subjects, and 10 patients (45.4%) showed co-infections. G. duodenalis was detected in 15 patients, in both mono- and co-infections, representing the most frequent pathogen, followed by enterotoxigenic Escherichia coli (ETEC) LT/ST. Four norovirus isolates were also detected and assigned to genogroups I and II. Conclusions: Considering the burden of enteric infections in developing countries, particularly among children, and the high rate of co-infections in asymptomatic subjects, this study shows the need for diagnostic tools such as xTAG GPP to improve diagnosis and treatment of these infections in endemic areas.